CRITICAL ANALYSIS OF THE ROLE OF PET-CT IN THE EVALUATION OF HEPATIC TUMORS - Nasser Muhanna Alanazi, Sara Fahad Alqhtani, Maram Hashem Almuhanna, Ghadeer Abdulrahman Al-Shalail, Raja Sughayir Ali Alasiri, Sharifa Mohammed A Hadi, Abdullah Awad Alnabani, Awad Hindi Alotaibi (Chelonian Research Foundation, 2022)
This article contains a detailed consideration of PET-CT, which plays a paramount role in evaluating liver tumors. Hematoma, a hepatic tumor involving primary liver cancer and metastatic lesions, has substantial diagnostic and treatment challenges. PET-CT is a hybrid imaging modality that melts together anatomy and function. This imaging machine was discovered to be a gold standard examination tool for assessing hepatic tumors. This investigation covers the clinical utility, weak points, and further prospects of PET-CT, mainly hepatic tumor evaluation methods, which provide a background for physicians who deal with patients with liver cancer. Keywords: PET-CT, hepatic malignant tumors, liver cancer, metastasis, imaging, diagnosis.